A retrospective economic vulnerability index, 1990-2011 - Using the 2012 UN-CDP definitions - Joël Cariolle; Michaël Goujon (Fondation pour les études et recherches sur le développement international (FERDI), 2013)
This document is aimed at presenting detailed calculation principles for annual retrospective series of the Economic Vulnerability Index according to the 2012 UN-CDP definitions. It is organized as successive technical sheets explaining EVI retrospective component calculation, reminding definitions followed by the UN-CDP in its 2012 Review of Least Developed Countries, and presenting adjustments that had to be made to obtain retrospective series. Retrospective series cover the 1990-2011 period (starting 1980 for some countries) and 130 developing countries (among which 48 LDCs and 82 non LDCs) and are gathered in the companion database.
Keywords: O11; C82; 330